Effects of online shopping values on website satisfaction among millennials in Klang Valley / Muhammad Muhaimin Shakir Azman - Azman, Muhammad Muhaimin Shakir (Faculty of Business and Management, 2020)
This paper aims to decode the effects of online shopping values on website satisfaction. Independent variable includes hedonic, utilitarian shopping value, website informativeness, entertainment, effectiveness of information content while web satisfaction as opposite site. The survey form was distributed via snowball sampling technique and a sample of 100 respondents were participated in the month of November 2019. The data analyzed using multiple regression analysis found that web informativeness is the most significant factor affecting website satisfaction.